1990
DOI: 10.1111/j.1476-5381.1990.tb12715.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic β1‐adrenoceptor antagonist treatment sensitizes β2‐adrenoceptors, but desensitizes M2‐muscarinic receptors in the human right atrium

Abstract: 1 In 64 patients undergoing coronary artery bypass grafting the effects of chronic fl1-adrenoceptor antagonist (metoprolol, atenolol, bisoprolol) treatment on right atrial fi-adrenoceptor and muscarinic M2-receptor number and functional responsiveness were investigated.2 The fil-adrenoceptor antagonists increased right atrial fl,-adrenoceptor number, did not affect fl2-adrenoceptor number, and decreased muscarinic M2-receptor number. 3 Concomitantly, activation of right atrial adenylate cyclase by 1OuM GTP, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 35 publications
(36 reference statements)
6
31
0
1
Order By: Relevance
“…None of the observed differences between groups before, during, and after treatment is statistically significant. adenylate cyclase activity were enhanced in right atria from patients that had been treated with 13l-selective adrenoceptor antagonists (Motomura et al, 1990). Similar findings have also been obtained in canine hearts where removal of the endogenous agonists by cardiac denervation also enhanced adenylate cyclase responsiveness (Vatner et al, 1985).…”
Section: Prostaglandin Elsupporting
confidence: 73%
“…None of the observed differences between groups before, during, and after treatment is statistically significant. adenylate cyclase activity were enhanced in right atria from patients that had been treated with 13l-selective adrenoceptor antagonists (Motomura et al, 1990). Similar findings have also been obtained in canine hearts where removal of the endogenous agonists by cardiac denervation also enhanced adenylate cyclase responsiveness (Vatner et al, 1985).…”
Section: Prostaglandin Elsupporting
confidence: 73%
“…Since the most important property of carvedilol is antioxidative profile and nebivolol predominantly effects nitric oxide (NO) pathway, the common protective pathway of nebivolol and carvedilol could be the intrinsinc beta blocker properties coupled to antioxidant and NO release. Previous studies showed that patients treated with β1-selective antagonists without intrinsic sympathomimetic activity (ISA) had more adrenoceptors than control subjects [44] and that the adenylate cyclase activation by the β-adrenoceptor agonist isoprenaline is also enhanced in this situation [45]. The ISA is therefore an important criterion for the therapeutical usefulness of BBs in heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some β-1 AR blockers such as metoprolol or bisoprolol have been shown to up-regulate β-AR in the heart of patients with CHF (Gilbert et al 1996;Heilbrunn et al 1989;Sigmund et al 1996;Waagstein et al 1989). Interestingly, several studies in patients with coronary artery disease have shown that chronic treatment with β-1 AR selective blockers such as metoprolol, atenolol or bisoprolol sensitizes cardiac β-2 AR function in vitro (Hall et al 1990;Motomura et al 1990) and in vivo (Hall et al 1991). Whether this occurs also in CHF patients and whether this may contribute to the beneficial effects of β-1 AR blockers in these patients is still a matter of debate.…”
Section: Effects On β-Adrenoceptor Densitymentioning
confidence: 99%